2021
DOI: 10.1038/s41598-021-92528-x
|View full text |Cite
|
Sign up to set email alerts
|

The gastrin-releasing peptide/bombesin system revisited by a reverse-evolutionary study considering Xenopus

Abstract: Bombesin is a putative antibacterial peptide isolated from the skin of the frog, Bombina bombina. Two related (bombesin-like) peptides, gastrin-releasing peptide (GRP) and neuromedin B (NMB) have been found in mammals. The history of GRP/bombesin discovery has caused little attention to be paid to the evolutionary relationship of GRP/bombesin and their receptors in vertebrates. We have classified the peptides and their receptors from the phylogenetic viewpoint using a newly established genetic database and bio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…Daum et al revealed that the skin secretion from the hybrid frog species, Pelophyla x kl. esculentus , could manifest a more potent fungicidal effect against Batrachochytrium dendrobatidis , along with a greater antimicrobial peptide diversity ( Hirooka et al, 2021 ). However, the hybrid amphibian systems are largely unstudied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daum et al revealed that the skin secretion from the hybrid frog species, Pelophyla x kl. esculentus , could manifest a more potent fungicidal effect against Batrachochytrium dendrobatidis , along with a greater antimicrobial peptide diversity ( Hirooka et al, 2021 ). However, the hybrid amphibian systems are largely unstudied.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrin-releasing peptides (GRP) and neuromedin-B (NMB) are two BLPs found in mammals ( Jensen et al, 2008 ). Originally isolated from porcine stomach, GRP stimulates gastrin release, smooth muscle contraction, and proliferation of epithelial cells ( Hirooka et al, 2021 ). NMB was latterly identified from porcine tissue and has been found to contract smooth muscles, influence endocrine secretion, and regulate blood pressure ( Hiroko, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bombesin and GRP were earlier considered orthologous among frogs and mammals. However, it is reported that in frogs, GRP exists separately from bombesin, suggesting that GRP is not a mammalian bombesin 25,26 . GRP is highly expressed in the hippocampus, 11 lateral amygdala, 11 accessory basal nucleus of the amygdala, 27 suprachiasmatic nucleus, 8 dorsomedial nucleus of the hypothalamus, 28 and dorsal root/trigeminal ganglion neurons 29 .…”
Section: Grp and Its Cognate Receptor Grprmentioning
confidence: 99%
“…Gastrin-releasing peptide (GRP) in somatosensory neurons encodes itch-specific information and can activate GRPR, a G q protein-coupled receptor (GPCR), in the spinal cord to transmit itch information in mice ( Barry et al, 2020 ; Chen, 2021 ; Sun and Chen, 2007 ; Sun et al, 2009 ). GRP is conserved across animal phyla, including mammals ( Hirooka et al, 2021 ; Takanami et al, 2022 ). Suprachiasmatic nucleus (SCN) GRP neurons are a subset of retinorecipient cells located in the ventrolateral side (the core area) and convey photic information directly from the retinohypothalamic tract (RHT) ( Abrahamson and Moore, 2001 ; Karatsoreos et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%